Reseñas bibliográficas 49-I (2016) - Brangier, Víctor; Enríquez, Lucrecia Raquel; Undurraga Schüler, Verónica; Boero Vargas, Mario; Ibarra Cifuentes, Patricio; Arias Gallegos, Walter; Ossa Santa Cruz, Juan Luis; Alburquerque, Germán; Hausser, Christian; Ovalle Pastén, Daniel; Serrano del Pozo, Gonzalo; Sanfuentes, Olaya; et al. (Historia, 2016)
Las "Reseñas bibliográficas" no contemplan resumen.